EXPOSITORY TEXTS ANTICIPATING CONTENT THROUGH QUESTIONS - Abdumajit Mamadaliev; Adiba Musayeva (Web of Journals Publishing, 2024)
Engaging with expository texts is a fundamental aspect of acquiring knowledge and developing critical thinking skills. However, passive reading can hinder comprehension and limit the reader's ability to extract key information. To overcome this challenge, one effective strategy is to anticipate content through the use of questions. By asking questions before and during the reading process, readers can activate their prior knowledge, focus their attention, and extract relevant information more effectively. This article explores the benefits of using questions to anticipate content in expository texts and provides strategies to enhance reader engagement and comprehension. Through this approach, readers can actively interact with the material, deepen their understanding, and develop critical thinking skills that are essential for successful navigation of expository texts.
Keywords: expository texts, acquiring knowledge, critical thinking, reading comprehension, key information, anticipate, interact, deepen understanding, successful navigation.